Media portrayal of mental health at the 2020 Tokyo Olympic and Paralympic Games - Keal, J.; McCabe, T.; Wright, J.; Renshaw, P. (Sports Psychiatry, 2022)
Introduction: The media coverage of high-profile sporting events can bring increased pressure to athletes` psychological wellbeing. There may be speculation regarding athletes` mental state before, during and after competition potentially impacting on both the athlete`s wellbeing and public perception of the individual if a negative tone is attached to an article. As mental health understanding and literacy develop, media reporting of elite athlete mental health may contribute to shaping of opinions and help seeking behaviour. Thus, we have aimed to understand and analyse the tone and content of media reporting on a high-profile sporting event using qualitative methods to explore key aspects of the articles sampled. Methods: We selected two UK broadsheet newspapers available online (The Guardian and The Telegraph) and identified all text articles including the terms "Mental Health" and "Olympics" or "Paralympics" published between 23rd July 2019 and 30th November 2021. We selected articles relevant to the Tokyo 2020 Olympic and Paralympic Games and including mental health as a subject. Relevant articles were read in full, and we conducted a thematic analysis to explore how mental health was portrayed. Results: 581 results were generated from our initial search. Following screening and removal of irrelevant articles, we had 95 articles for analysis. We identified four themes relating to portrayal of mental health: Pressure, impact of COVID, Lack of specific diagnostic terms, and athletes as humans. Conclusion: Media portrayal of mental health at the Tokyo Games was generally positive and portrayed athletes as relatable, inspiring, and "human" rather than superhuman. Reporting particularly focused on athlete-specific factors in mental health conditions and the pressures of high-level competition.